GRAFICZNY INTERFEJS UŻYTKOWNIKA I FUNKCJONALNOŚĆ WIRTUALNYCH WYCIECZEK NA WYBRANYCH PRZYKŁADACH - Pilarska, Agnieszka; Tymczykowska, Paulina (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2025)
The aim of this paper is to characterize the graphical interface and functionality of virtual tour applications. The indirect aim is to provide initial technical assessment of selected virtual tours avaialable on Polish websites. In addition, the article presents the importance of the terms related to multimedia presentation of online tourist content. References have been made to concepts such as geoinformation society, geoinformation, geospatial data, interactive panoramas and tourism space. In the research, descriptive and comparative methods were used. The initial technical assessment was made by means of the Web Page Analyzer – 0.98 (http://www.websiteoptimization.com/services/analyze) from Website Optimization. Results Research into the interface, the functionality and technical assessment revealed that the selected virtual tour applications available online are very diverse. The differences exist both on the quantitative and the qualitative levels. The results have led to a conclusion that the Internet infrastructure, with special emphasis placed on the geo-information infrastructure, allows to develop and transfer tourist activity to the virtual world. The progressive functionality and ergonomics of the interfaces enable multimedia presentations in the form of virtual tours, including use of 360º panoramas, to reach an increasingly wide audience with diverse interests.